The perceptions of professional soccer players on the risk of injury from competition and training on natural grass and 3rd generation artificial turf - Poulos, C. C. N.; Gallucci, J.; Gage, W. H.; Baker, J.; Buitrago, S.; Macpherson, A. K. (BMC Sports Science, Medicine and Rehabilitation, 2014)
The purpose of this study was to describe professional soccer players` perceptions towards injuries, physical recovery and the effect of surface related factors on injury resulting from soccer participation on 3rd generation artificial turf (FT) compared to natural grass (NG).